Case Study in Network Security System Using Random Port Knocking Method on The Principles of Availability, Confidentiality and Integrity - Ernawati, Tati; Idham Kholid; Dahlan; Rohmayani, Dini (JOIN (Jurnal Online Informatika), 2024)
Preventing unidentified individuals from misusing their access to information is a major concern when it comes to data security. Network administrators are charged with working harder to be able to secure the computer network they manage. The utilization of right method is a challenge for network administrators to protect computer network from intruders. The RPK method is one of solution to overcome this problem. This research aims to implement RPK method on the principles of availability, confidentiality, and integrity which have not been explored by previous studies. The network system configuration stage involved installing Debian 9, NMAP, Hydra, RPK, cloud server, remote admin, and attacker. The network security system's performance was tested, revealing a 99.97% availability rate and 100% confidentiality. The system's integrity was assessed, with an average response time of 0.22 seconds and 100% blocking accuracy. The test results indicate that the system's network security performance, using the RPK method, capable of protecting server attacks and effectively upholding security stability.